К изучению постэмбрионального развития пластинокрыла обыкновенного — Phaneroptera falcata Роda. (Tettigoniidae, Orthoptera) - Добош, И.Г. (Вестник зоологии, 1969)
In the development of Phaneroptera falcata larva there are six ages; the larvae of each age differ in the body size, pronotum form, degree of development and position of the wing pads and folds of the ovipositor. Each age lasts for almost the same period (approximately 8—10 days).